Pemberdayaan Perempuan melalui Kelompok Wanita Tani (KWT) Kinanti di Desa Lumajang, Kecamatan Watumalang, Kabupaten Wonosobo - Arbian, Wafiq Nur; Wardani , Dyah Puspito (Jurnal Ilmu-Ilmu Pertanian, 2025)
This study aimed to examine the process of women's empowerment through the activities of the Kinanti Women's Farming Group (Kelompok Wanita Tani/KWT) in Lumajang Village, Watumalang District, Wonosobo Regency. KWT serves as a participatory platform for rural women to enhance household economic capacity through horticultural seedling activities and post-harvest processing. The research employed a qualitative approach with a case study method. Data were collected through field observations, in-depth interviews, and institutional document analysis. The findings reveal that KWT Kinanti has successfully improved members’ technical skills, expanded vegetable seedling marketing networks, and contributed significantly to household income. The empowerment process observed has impacted not only the economic aspect but also strengthened self-confidence, social solidarity, and women's participation in village development. This study highlights the importance of strengthening gender-based local institutions to support sustainable agriculture in rural areas.